2023
DOI: 10.3390/jcm12103399
|View full text |Cite
|
Sign up to set email alerts
|

Joint Response to Exercise Is Affected by Knee Osteoarthritis: An Infrared Thermography Analysis

Abstract: Infrared thermography can be used to evaluate the inflammation characterizing the joint environment of OA knees, but there is limited evidence on the response to physical exercise. Identifying the response to exercise of OA knees and the influencing variables could provide important information to better profile patients with different knee OA patterns. Sixty consecutive patients (38 men/22 women, 61.4 ± 9.2 years) with symptomatic knee OA were enrolled. Patients were evaluated with a standardized protocol usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…A recent study observed that in postmenopausal women, physical effort has been positively associated with amelioration in coordination, balance, flexibility, muscle strength, and bone mineral density [41]. In addition, de Marziani et al observed that women showed a greater temperature decrease than men when they were evaluated with a thermographic camera, directly after and five minutes after a 2 min knee flexion-extension exercise [43]. Another study aimed to evaluate the impact of sex on the effectiveness of platelet-rich plasma (PRP) in KOA patients.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study observed that in postmenopausal women, physical effort has been positively associated with amelioration in coordination, balance, flexibility, muscle strength, and bone mineral density [41]. In addition, de Marziani et al observed that women showed a greater temperature decrease than men when they were evaluated with a thermographic camera, directly after and five minutes after a 2 min knee flexion-extension exercise [43]. Another study aimed to evaluate the impact of sex on the effectiveness of platelet-rich plasma (PRP) in KOA patients.…”
Section: Discussionmentioning
confidence: 99%
“…They represent one of the most common causes of knee pain and performance deterioration in athletes, with studies showing a higher incidence of knee OA in athletes compared to the general population [1,22,40,45]. This is ascribable to the continuous cartilage solicitation and frequent overuse injuries during physical activity, leading to its premature degeneration, joint inflammation, and ultimately favouring the early development of OA [15,16,30,45]. These patients can experience symptoms ranging from knee pain and loss of function, which negatively impact their sport activity, resulting in reduced performance and even early retirement from sport [55].…”
Section: Introductionmentioning
confidence: 99%